Pricing Model - Aware Task Scheduling in Cloud paradigm enhanced with DRL on MAPE Framework - D. R. Umesh , Shruthi P. S., (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing being a multifarious technology offers greater services to the end users, on a serious note several challenges need to be addressed to date even though numerous researches have been conducted in this field. Among the major issues like security, sustainability, availability, and many more, efficient resource allocation according to the requirement is important. Efficient resource allocation has become a critical issue in cloud computing because over-provisioning increases financial risk both at the provider’s site and end-user; under-provisioning increases the service latency it may violate service level agreements eventually providers lose their customers. Hence many research works are going on to come up with an optimal solution for resource allocation in the cloud paradigm in different ways, like load balancing, workflow scheduling, container positioning, QOS parameter-based scheduling, etc. Our work addresses the task secluding by using the Deep Reinforcement technique corresponding with MAPE architecture, where the process of task scheduling is evolved over the various stages of MAPE architecture combining the VM pricing models (reserve, on-demand, and spot). We implemented our technique on the BitBrains dataset which consists of traces of 1750 VM. The results are discussed on variants of Reinforcement techniques and concluded the Reinforcement combining with neural network i.e DeepReinforcement technique with VM pricing model (DRL with PM) shows better results compared to other techniques. Our work’s throughput is compared to those of others who achieved promising results, validating that our approach to task scheduling yields superior outcomes.